Novel HMO-Glasses with Sb2O3 and TeO2 for Nuclear Radiation Shielding Purposes: A Comparative Analysis with Traditional and Novel Shields - ALMisned, Ghada; Tekin, Huseyin Ozan; Issa, Shams A. M.; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin; Kilic, Gokhan; Zakaly, Hesham M. H.; Ene, Antoaneta (MDPI, 2021)
The radiation shielding characteristics of samples from two TeO2 and Sb2O3-based basic glass groups were investigated in this research. TeO2 and Sb2O3-based glasses were determined in the research as six samples with a composition of 10WO(3)-(x)MoO3-(90 - x)(TeO2/Sb2O3) (x = 10, 20, 30). A general purpose MCNPX Monte Carlo code and Phy-X/PSD platform were used to estimate the radiation shielding characteristics. Accordingly, the linear and mass attenuation coefficients, half value layer, mean free path, variation of the effective atomic number with photon energy, exposure and built-up energy factors, and effective removal cross-section values were determined. It was determined that the results that were produced using the two different techniques were consistent. Based on the collected data, the most remarkable findings were found to be associated with the sample classified as T80 (10WO(3) + 10MoO(3) + 80TeO(2)). The current study showed that material density was as equally important as composition in modifying radiation shielding characteristics. With the T80 sample with the greatest density (5.61 g/cm(3)) achieving the best results. Additionally, the acquired findings were compared to the radiation shielding characteristics of various glass and concrete materials. Increasing the quantity of MoO3 additive, a known heavy metal oxide, in these TeO2 and Sb2O3-based glasses may have a detrimental impact on the change in radiation shielding characteristics.
Keywords: HMO glasses; radiation shielding; TeO2; Sb2O3; HEAVY-METAL OXIDES; GAMMA; NEUTRON; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics